Leadership : regional and global perspectives - Muenjohn, Nuttawuth; McMurray, Adela; Fernando, Mario, 1965-; Hunt , James G., 1932-; Fitzgerald, Martin; McKenna, Bernard, 1952-; Intezari, Ali; Bankins, Sarah; Waterhouse, Jenny (Cambridge : Cambridge University Press, 2018)
Whether leading a small team or a multinational corporation, within the public or private sector, a thorough understanding of the theory and best practice of leadership is essential. Leadership: Regional and Global Perspectives provides a fresh approach to leading in contemporary business environments. The theory component is complemented by a focus on strategic application. Each chapter features case studies highlighting the practical application of key concepts by organisational leaders in the Australasian region. Case studies at the end of each chapter provide a more nuanced analysis of the theory, while accompanying questions encourage students to think critically. Learning is further supported through the inclusion of learning objectives, key terms, further readings and review questions. An extensive bank of web resources is available to lecturers to support their teaching. Written by an expert team of academics from across Australia, Leadership gives students the tools they need to navigate their leadership journey.
Title from publisher's bibliographic system (viewed on 26 Mar 2019).
Keywords: elektronické knihy; electronic books; Leadership; Industrial management; Organizational effectiveness